Children’s Responses to Divergent and Convergent Design Feedback - Schut, Alice; Klapwijk, Remke; Gielen, Mathieu; Vries, Marc de (Design and Technology Education: An International Journal, 2019)
In this paper, we explore the divergent and convergent nature of design feedback and the various responses to this feedback from a group of 24 young novice designers (primary school children age 9-11) taking part in a co-design project. Earlier research emphasizes that feedback can encourage a designer to take divergent as well as convergent paths during their design process (Cardoso, Eris, Badke-schaub, & Aurisicchio, 2014; Yilmaz & Daly, 2014, 2016). Yet our previous research shows, that feedback given to primary school children while designing does not always spark creative thinking (Schut, Klapwijk, Gielen, Van Doorn, & De Vries, 2019). We presume that the responses we found might have been influenced by the type of feedback that preceded them. Therefore, we have elaborated on the results we’ve previously uncovered with an additional analysis of the same case study. This additional analysis shows that divergent feedback given by peers or a client will not necessarily promote divergent thinking processes, whereas convergent feedback will not necessarily promote convergent thinking. Furthermore, responses indicating resistance towards the feedback given were widespread. However, we believe that feedback from clients and peers can still be a fruitful strategy in learning to be creative and in promoting divergent thinking (DT) and convergent thinking (CT) and end with suggestions on how this might be achieved.